Kesetaraan Gender di Dunia Industri Kota Tangerang - Sahda Febbina Shalim; Rini Sulastri (UIN Sunan Gunung Djati Bandung, 2024)
Gender differences are actually not a problem as long as they do not lead to gender injustice. However, in reality, gender differences have led to various forms of injustice, not only against men but also especially against women. The forms of gender injustice that women get are factors that influence women taking part in the world of work. The interesting thing to study in this mini research is the problem of discrimination of women in the world of labor. although women work, their work is considered a side job. Women's position is defined by their relationship with men. The purpose of this research is to find out the forms of gender injustice experienced by women in the world of employment and what factors are obstacles to women taking part in the labor industry sector in Indonesia. Researchers used a descriptive qualitative approach method to find out directly, in detail and in reality the state of the object in accordance with the conditions of the research site. Gender inequality is reflected in various forms of inequality such as stereotyping, double burden, marginalization, and acts of violence. The low level of education obtained by women makes them unable to compete in the industrial sector.